Method of lines analysis of Dufour and Soret effects on unsteady MHD free convective heat and mass transport flow past a porous infinite plate - Ugwu*†, U.C.; Cole*, A.T.; Faruk*, A.I.; Adedayo*, O.A.; Asonibare*, F.I.; Egbugha‡, M.C. (International Journal of Mathematical Analysis and Modelling, 2023)
The problem of coupled heat and mass transfer by free convection of a chemically reacting viscous incompressible and electrically conducting fluid past an infinite vertical porous plate under the influence of uniform transverse magnate field in the presence of diffusion-thermo (Dufour), thermal-diffusion (Soret) and internal heat source or sink is studied. A magnetic field of uniform strength is applied perpendicular to the plate and the fluid is subjected to a normal suction velocity while the heat flux at the plate is constant. The dimensionless governing equations were solved numerically in MATLAB using the Method of Lines (MOL). Some of the results indicating the influence of various thermos-physical parameters of fluid flow, heat and mass transfer characteristics were obtained and presented graphically. The numerical values of skin-friction coefficient and Nusselt number at the plate are derived, discussed numerically for various values of physical parameters and presented through tables. The presence of a generating heat source has effects on the fluid velocity, as well as on temperature.